The Key English Language Skills Needed by Eleventh Grade Hospitality Students at SMKN 1 Sukasada - Ni Kadek Chandra Maharani; Ni Wayan Surya Mahayanti; Ni Luh Putu Era Adnyayanti (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
Careers in the hospitality industry require strong English communication skills, particularly in speaking. This study aims to identify the English language skills needed by eleventh-grade hospitality students at SMKN 1 Sukasada. A qualitative descriptive method was employed, involving 13 purposively selected students. Data were collected through both closed- and open-ended questionnaires and analyzed descriptively. The findings revealed that speaking is perceived as the most essential skill in hospitality, yet students have limited exposure to English in their daily lives. Major challenges identified include limited vocabulary, difficulties with pronunciation, and low self-confidence. Therefore, the study recommends increasing English exposure outside the classroom, incorporating more speaking-focused activities, and providing targeted vocabulary and pronunciation practice. A supportive learning environment is also crucial for enhancing these skills. Despite its small sample size, this study provides valuable insights for the development of English curricula that address the specific communicative needs of vocational hospitality students.